DELINEATING THE ROLE OF SOLUBLE CD25 AS AN IMMUNOREGULATORY MOLECULE THAT PROMOTES A LOW-ZONE IL-2 SIGNALING ENVIRONMENT FAVORABLE FOR THE SELECTION OF CD25HIGH FOXP3HIGH T CELLS - Nickle, Rebecca Ann (East Carolina University, 2021)
Autoimmune diseases develop due to the breakdown of tolerogenic mechanisms that normally maintain immune homeostasis. CD4+ CD25+ FOXP3+ regulatory T cells (Tregs) are critical in the maintenance of tolerance and the inhibition of autoimmunity. However, in autoimmunity, Tregs are dysfunctional in their suppressive abilities and/or deficient in numbers. Tregs are classically defined by their constitutively high expression of CD25 and FOXP3, which govern and stabilize their suppressive phenotype. Current treatments for autoimmunity and chronic inflammation focus on broad immunosuppression and symptom management that do little to restore self-tolerance. Newly emerging immunotherapies aim to restore homeostasis through ex vivo and in vivo manipulation of Treg populations. However, due to the phenotypic instability of Tregs, such therapies face many obstacles. During in vitro activation and propagation of T cells in the presence of IL-2, FOXP3+ Tregs are rapidly overgrown by FOXP3- conventional T cells (Tcons). However, recent advances have discovered a low-zone IL-2 signaling window, whereby Tregs outcompete Tcons for available IL-2 due to a differential expression of CD25. In this study, we defined the physiologically relevant serum protein, soluble CD25 (sCD25), as an immunoregulatory molecule that antagonizes and prolongs the bioavailability of IL-2 to promote low-zone IL-2 signaling environments favorable for the survival and expansion of CD25high FOXP3high T cells. During T cell activation, sCD25 blocked IL-2-induced CD25 expression, thus limiting activation-induced T cell expansion. In post-activation cultures, the low-zone IL-2 environment, mediated by sCD25, blocked IL-2 signaling in CD25low T cells but not CD25high T cells, allowing for competitive outgrowth of CD25high T cell populations. Additionally, these studies developed two novel monoclonal antibodies (mAbs) specific for human CD25 that are useful for the cytometric identification of transmembrane and soluble forms of human CD25. These studies provide novel tools for the identification of human CD25 and provide a novel role for sCD25 as a tool to drive low-zone IL-2 signaling environments favorable for the ex vivo stabilization of human CD25high FOXP3high Tregs. Importantly, these studies also provide a more complete understanding of the role of sCD25 in immunological disease and its potential therapeutic efficacy in controlling chronic inflammation.
Keywords: soluble CD25; Tregs; autoimmunity; monoclonal antibody; immunoregulatory; low-zone Il-2 signaling; T-Lymphocytes; Interleukin-2 Receptor alpha Subunit; Receptors, Interleukin-2